Biofunctionalized nanoparticles: an emerging drug delivery platform for various disease treatments. Issue 8 (August 2016) - Bose, Rajendran J.C.; Lee, Soo-Hong; Park, Hansoo
Highlights: Biofunctionalization with cell membranes gives cell like functions to NPs. Cell membranes can be used for targeted drug delivery. Preparations, characterization and application of cell membrane functionalized NPs are detailed. The challenges and opportunities are presented. Abstract : Biological barriers, such as phagocytosis and nonspecific distribution, are major factors limiting the clinical translation of nanomedicine. Biomimetic and bioengineering strategies have been used to overcome these challenges. In particular, natural cell membrane-based biofunctionalized nanoparticles (CMFNPs) have gained widespread attention owing to their cell surface mimetic characteristics and tailored nanomaterial features. These hybrid nanocarriers show strong potential for the delivery of myriad therapeutic agents. Herein, we highlight the most recent advances in CMFNP-based drug delivery systems and address the challenges and opportunities in the field.